2022
DOI: 10.1016/j.psj.2021.101647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic macro and trace minerals in fast and slower growing broiler breeders’ diet on offspring growth performance and tibia characteristics

Abstract: This study was designed to evaluate effects of source of macro and trace minerals (inorganic vs. organic) in fast and slower growing broiler breeders’ diets on egg and hatchling mineral content and on offspring tibia morphological, biophysical, and mechanical characteristics. After 10 wk feeding the breeders (at 30 wk of age), eggs were collected and incubated. Eggs and hatchlings were analysed on mineral content. Male chickens were assigned to 32 pens with 12 chickens per pen. At approximately 1,700 and 2,600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, focusing on well-being and housing conditions, chicken meat production is more oriented towards less intensive systems, for which medium- and slow-growing broiler strains have been recommended [ 7 ]. In fact, medium- and slow-growing chickens are more suitable for alternative production systems for their higher vitality, disease resistance, and adaptability to outdoor conditions than fast-growing chickens [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, focusing on well-being and housing conditions, chicken meat production is more oriented towards less intensive systems, for which medium- and slow-growing broiler strains have been recommended [ 7 ]. In fact, medium- and slow-growing chickens are more suitable for alternative production systems for their higher vitality, disease resistance, and adaptability to outdoor conditions than fast-growing chickens [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…( 2015 ) showed that genetic factors determining faster growth also led to heavier, longer and wider leg bones in broilers. However, some researchers (Güz et al., 2022 ; van der Eijk et al., 2022 ) showed that slow‐growing broilers have better tibia morphological characteristics compared to fast‐growing broilers at the same body weight. This discrepancy among studies is likely explained by sampling at different ages and body weights.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, 100 mg/kg OPC increased the content of Ca and P of femur and tibia, but the ratio of Ca and P remained unchanged. Furthermore, trace minerals also plays a crucial role in the bone development of poultry ( M'Sadeq et al, 2018 ; Güz et al, 2022 ). Fe, Mg, Cu, and Mn plays a vital role in the growth and development of poultry, and cannot be underestimated in the formation of bone tissue and maintenance of bone health ( Sun et al, 2015 ; Echeverry et al, 2016 ; Byrne and Murphy, 2022 ).…”
Section: Discussionmentioning
confidence: 99%